Salman Rushdie Superstar: The Making of Postcolonial Literary Stardom - Mendes, Ana Cristina (2017)
“Known across the world for his flamboyance and... err... luck with the ladies, as much [sic] for his writing skills,” as Purnima Sharma puts it in The Times of India, Rushdie and his complex standing as literary star is well illustrated by his cameo appearance in Scarlet Johansson’s music video, and by the ‘chick magnet’ label that has come most visibly to attach itself to the writer since his fourth divorce. Reiterating the question posed by the reporter in the Sunday Times article, what indeed is “the pull”? What social meanings are behind Rushdie’s pulling power? What makes the Indian-born writer the object of such frequent media attention and headline-grabbing? At the same time, why would this acclaimed postcolonial author be so willing to allow his image to be used to advertise the launching of Johansson’s new artistic pursuit, when he gladly abandoned a career in the advertising industry in the 1980s? What ramifications might this phenomenon hold for the field of postcolonial cultural production? The broad purpose of this essay is to offer tentative answers to these questions from a critical standpoint that approaches celebrity as a commodity. There has been a surge of celebrity studies since the 1960s, including the pioneering works The Image by Daniel Boorstin and The Society of the Spectacle by Guy Debord, as well as Stars by Richard Dyer, The Frenzy of Renown by Leo Braudy, and Celebrity and Power by P. David Marshall. Although these works remain central to star studies today, they failed to address comprehensively the specific issue of literary fame.